Assessing the impact of antimicrobial stewardship programs in tertiary hospitals for UTI: does it work alone? - Yuri, Prahara; Shigemura, Katsumi; Dahesihdewi, Andaru; Zulfiqqar, Andy; Kitagawa, Koichi; Fujisawa, Masato (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Antibiotic resistance is currently an emergent global challenge. Urinary tract infection (UTI), one of the most commonly reported infections, are is becoming a difficult case to treat considering the increasing prevalence of antimicrobial resistance (AMR). The objective of this study was to assess the impact of a hospital antibiotic stewardship program on AMR in managing UTI at a tertiary referral hospital in Yogyakarta, Indonesia, while considering the absence of the program in lower-tier referral hospitals. A retrospective cross-sectional study was conducted from January 2017 to December 2020, classified into pediatric and adult samples. Urine samples were collected and cultured from all patients with UTI hospitalized in the Dr. Sardjito General Hospital, Yogyakarta. The UTI causative bacteria and antibiotic susceptibilities were investigated in the comparison of the first 2 years (2017-2018, prior to the hospital antibiotic stewardship program) and the last 2 years (2019-2020, following the implementation of the hospital antibiotic stewardship program). The isolates from 717 adult urine samples were cultured. Escherichia coli (39.1%), Acitenobacter baumanii (9.3%), and Pseudomonas aeruginosa (8.5%) were identified as the most common bacteria prior to the hospital antibiotic stewardship program. Extended-spectrum β-lactamase-producing E. coli and Burkholderia cepacia were still increasing in the following the implementation of the hospital antibiotic stewardship program. Our study indicated that the stewardship program does not exhibit a significant change during the first two years considering the absence of the program in lower-tier referral hospitals.